Certain classes of solutions of Lagerstrom equations - Omerspahić, Alma; Hadžiabdić, Vahidin (Sarajevo Journal of Mathematics, 2024)
This paper presents sufficient conditions for the existence of solutions for certain classes of Cauchy's solutions of the Lagerstrom equation as well as their behavior. Behavior of integral curves in the neighborhoods of an arbitrary or integral curve are considered. The obtained results contain the answer to the question on approximation of solutions whose existence is established. The errors of the approximation are defined by functions that can be sufficiently small. The theory of qualitative analysis of differential equations and topological retraction method are used.